Distance E-Learning (DEL) and Communication Studies During Covid-19 Pandemic - SNOUSSI, THOURAYA; RADWAN, AHMED FAROUK (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study explores the Distance E-Learning (DEL) experience of Communication students during the Coronavirus pandemic, in the United Arab Emirates (UAE), and measures the appropriateness of online remote technologies for media and communication courses. The data revealed several advantages that lie mainly in harnessing technologies, enhancing students' communication skills, and saving teaching and learning in times of crisis. The limits are mainly related to technical issues and computer proficiency. The findings from this study provide important input towards designing effective open online courses for communication students not only in the University of Sharjah but also in the world.RESUMEN Este estudio explora la experiencia de aprendizaje electrónico a distancia (DEL) de los estudiantes de comunicación durante la pandemia del coronavirus, en los Emiratos Árabes Unidos (EAU), y mide la idoneidad de las tecnologías remotas en línea para los cursos de medios y comunicación. Los datos revelaron varias ventajas que se encuentran principalmente en aprovechar las tecnologías, mejorar las habilidades de comunicación de los estudiantes y salvar la enseñanza y el aprendizaje en tiempos de crisis. Los límites están relacionados principalmente con problemas técnicos y competencia informática. Los hallazgos de este estudio proporcionan información importante para el diseño de cursos en línea, abiertos y efectivos para estudiantes de comunicación no solo en la Universidad de Sharjah sino también en el mundo.